The Occurrence of Sequences Identical with Epitopes from the Allergen Pen a 1.0102 Among Food and Non-Food Proteins - Minkiewicz Piotr; Sokolowska Jolanta; Darewicz Malgorzata (Polish Journal of Food and Nutrition Sciences)
The presence of common epitopes among tropomyosins of invertebrates, including arthropods, e.g. edible ones, may help to explain the molecular basis of cross-reactivity between allergens. The work presented is the first survey concerning global distribution of epitopes from Pen a 1.0102 in universal proteome. In the group of known tropomyosin epitopes, the fragment with the sequence ESKIVELEEEL was found in the sequence of channel catfish (Ictalurus punctatus) tropomyosin. To date, this is the first result suggesting the presence of a complete sequential epitope interacting with gE in vertebrate tropomyosin. Another fragment with the sequence VAALNRRIQL, a major part of the epitope, was found in 11 fish, 8 amphibians, 3 birds, 19 mammalians and 4 human tropomyosin sequences. Identical epitopes are common in sequences of invertebrate tropomyosins, including food and non-food allergens annotated in the Allergome database. The rare pentapeptide with the DEERM sequence occurs in proteins not sharing homology with tropomyosins. Pathogenic microorganisms are the most abundant category of organisms synthesizing such proteins.